Is home blood pressure monitoring feasible and well accepted in nephrectomized patients for renal cancer? (STAFF study). (April 2015) - Lorcy, Nolwenn; Dourmap-Collas, Caroline; Lafourcade, Alexandre; Le Stum, Sylvie; Victor, Brigitte; Donal, Erwan; Laguerre, Brigitte; Verhoest, Gregory; Oger, Emmanuel; Vigneau, Cécile
Abstract: Aims : Few studies have looked at blood pressure (BP) evolution after nephrectomy, except for in living kidney donors with no clinical relevant modifications. STAFF is a pilot, open-label, observational study to evaluate the feasibility of following BP by home blood pressure monitoring (HBPM) after nephrectomy for cancer. Major findings: 56 patients (66.1% previously treated for hypertension) were included between November 1, 2011, and December 31, 2012; 95.8% of the patients realized five of six primary end-points in HBPM, but the last monitoring session at 6 months was often lacking (60%) probably because of a lack of understanding. When BP was controlled before surgery, 36% of the patients underwent new hypertension or hypertension dysregulation, without any correlating factor found; 33% of the patients presented the presence of proteinuria or an increase during the follow-up. Previous hypertension or high body mass index were risk factors for proteinuria increase ( p = 0.036 and 0.032) but not treatment by an renin–angiotensin system blocker. There was no statistical link between HTA control and proteinuria. Conclusion : Our study shows that most patients undergoing nephrectomy for cancer are able to follow HBPM. It should be encouraged for detecting high BP or proteinuria, especially if antiangiogenic therapies are envisaged because of the supplementary risk of hypertension and proteinuria induced by these treatments.